Students’ Perception Toward The Implementation Of The TOEFL Test As Requirement For Graduation - yanto yanto (English Language, Linguistics, Literature, And Education Journal, 2019)
The purposes of this qualitative study were to explore students’ perception toward the implementation of TOEFL test as requirement for graduation by Medical Students at University of Jambi and to find out their readiness toward the test. Data for this study were collected through a demographic background, document analysis, and interview. The demographic data and document analysis were analyzed descriptively. The interviews data were analyzed by using thematic analysis. There were three students and a head of Medical study program as participants in interviews. Based on the research results, there were six major sub themes appeared on the data related to the voices of participants about the implementation of TOEFL test for Medical students such as opinion about TOEFL, TOEFL as requirement for graduation, the impact of TOEFL test, relationship between English and Medical discipline, benefit of English, and self preparation for TOEFL test.